Pengaruh Latar Belakang Ekonomi Orang Tua Terhadap Proses Belajar Dalam Perkembangan Sosial Emosional Siswa Di Paud Al-Fatih Lubuklinggau - Kamsi, Nurlila; Ertati, Ertati (STAI Bumi Silampari, 2024)
This research explains the role of parents in raising children in terms of the importance of thaharah values. The role of parents is very important in shaping children’s perceptions of thaharah. They are role models in carrying out purification rituals, understanding the importance of maintaining cleanliness, and conveying religious teachings in the steps of thaharah. With consistency and support, parents can help children understan the value of cleanliness in a religious context. Thaharah or purification is an important topic in Islamic law. The purpose of this research is to determine the role of parents towards their children in instiling thaharah values. Instiling attidues and behavior based on religious and moral values so that children can live in accordance with values aadopted by society, helping children grow into mature and independets individuals, instilling good manners and teaching children to love and maintain a clean environment and lovw hwalth. Literature riview with a qualitative approach. This type of research was carride out by reading, undrestangding, studying and examining the literature with the aim of finding out the importance of the tharah values that parents instill in their children.